Assessment of the Characteristics of Domestic Violence Presenting to Emergency Department in a Tertiary Care Hospital in Pakistan - Rabail Altaf, Pushpa, Mansoor Ali, Haya Afzal, Muhammad Ayob, Pardeep Kumar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Domestic violence is a pervasive global issue and a recognized public health concern in Pakistan. Here we present the characteristics of domestic violence victims presenting to the emergency department. Methodology: A cross-sectional study was conducted in one of the tertiary care hospitals in Pakistan. The study analyzes the characteristics of domestic violence presented in the hospital’s emergency department and also determines the prevalence and the demographics of the victims. Results: The study with a total of 124 participants, revealed a distressingly high incidence of domestic violence, with 78.2% of participants reporting experiencing Domestic Violence (DV) at some point in their lives. Among various forms of DV, the most prevalent included being slapped (25.8%), pushed (15.3%), and kicked (14.5%). Furthermore, threats (14.5%), weapon use (4.8%), child abuse (10.5%), neglect (2.4%), and shouting (8.9%) were also documented. These findings highlight the diverse and troubling nature of domestic violence, affecting individuals both physically and psychologically. Conclusion: Despite the study’s limitations, including a small sample size and convenient sampling technique, the findings provide valuable insights into the widespread and complex nature of domestic violence in Pakistan, influenced by cultural norms. Collaboration among healthcare providers, policymakers, and the community is vital to address this pressing public health issue and protect vulnerable individuals, especially women who are disproportionately affected. Keywords: domestic violence, intimate partner violence, abuse, neglect